2020
DOI: 10.1021/acsomega.0c02072
|View full text |Cite|
|
Sign up to set email alerts
|

Nanostructured Lipid Carriers Delivering Sorafenib to Enhance Immunotherapy Induced by Doxorubicin for Effective Esophagus Cancer Therapy

Abstract: The tumor microenvironment (TME) plays a significant role in weakening the effect of cancer immunotherapy, which calls for the remodeling of TME. Herein, we fabricated a nanostructured lipid carrier (NLC) to codeliver doxorubicin (Dox) and sorafenib (Sfn) as a drug delivery system (NLC/D-S). The Sfn was expected to regulate the TME of esophagus cancer. As a result, the immune response induced by Dox-related immunogenicity cell death could be fully realized. Our results demonstrated that Sfn was able to remodel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In another study, an inhalable drug delivery system using NLCs loaded with doxorubicin, siRNA, and conjugated LHRH peptide showed better control of cancer cells than intravenous injections ( Table 3 ) [ 239 ]. Further, researchers found that NLC fabricated with doxorubicin and sorafenib can stimulate PD-1 expression, down-regulate Treg cells, activate effector T cells, and regenerate the immune response ( Table 4 ) while inhibiting esophagus tumors by bypassing the TME [ 240 ].…”
Section: Novel Nanocarriers Based Treatment Approachmentioning
confidence: 99%
“…In another study, an inhalable drug delivery system using NLCs loaded with doxorubicin, siRNA, and conjugated LHRH peptide showed better control of cancer cells than intravenous injections ( Table 3 ) [ 239 ]. Further, researchers found that NLC fabricated with doxorubicin and sorafenib can stimulate PD-1 expression, down-regulate Treg cells, activate effector T cells, and regenerate the immune response ( Table 4 ) while inhibiting esophagus tumors by bypassing the TME [ 240 ].…”
Section: Novel Nanocarriers Based Treatment Approachmentioning
confidence: 99%
“…SOR-loaded NLC-A/B exhibited stronger antitumor activity than free SOR. Wang et al fabricated NLCs to co-deliver doxorubicin (DOX) and SOR 72 . With the combination of DOX-induced immunogenic cell death and SOR-mediated tumor microenvironment (TME) remodeling, the NPs showed strong anticancer benefits and immune response after treatment.…”
Section: Enhancing the Biocompatibility Of Sor With Npsmentioning
confidence: 99%
“…For this purpose, NLCs are being employed for targeting tumors. NLCs have been developed for the co-delivery of DOX and sorafenib (Sfn), where Sfn was expected to remodel the TME, consequently enhance the immunotherapy, which was then stimulated by DOX for successful esophagus cancer therapy ( Wang et al., 2020 ).…”
Section: Focus Of Current Lipid-based Theranostic Approachesmentioning
confidence: 99%